Cadmium Accumulation Characteristics in Turnip Landraces from China and Assessment of Their Phytoremediation Potential for Contaminated Soils - Li, Xiong; Zhang, Xiaoming; Yang, Ya; Li, Boqun; Wu, Yuansheng; Sun, Hang; Yang, Yongping (Frontiers in Plant Science, 2016)
Heavy metal (HM) pollution is a global environmental problem that threatens ecosystem and human health. Cadmium (Cd) pollution is the most prominent HM pollution type because of its high toxicity, strong migration, and the large polluted area globally. Phytoremediation of contaminated soil is frequently practiced because of its cost-effectiveness and operability and because it has no associated secondary pollution. High-accumulation plants, including those identified as hyperaccumulators, play an important role in phytoremediation. Therefore, screening of plants to identify hyperaccumulators is important for continued phytoremediation. In the present study, we investigated the Cd tolerance and accumulation capabilities of 18 turnip landraces from China under a soil experiment with known Cd level. The results indicated that turnip has a high capacity for Cd accumulation. Furthermore, significant differences in Cd tolerance and accumulation characteristics were found among different landraces when they grew at 50 mg kg−1 (dry weight) Cd concentration. Among the studied landraces, five turnip landraces met the requirements of Cd hyperaccumulators and three landraces were identified as potential candidates. However, the total Cd content accumulated by individual plant of different turnip landraces was dependent on both the Cd accumulation capacity and plant biomass. Compared with some reported Cd hyperaccumulators, turnip not only shows a high Cd-accumulation capacity but also has rapid growth and a wide distribution area. These advantages indicate that turnip may have considerable potential for phytoremediation of Cd-contaminated soil. Furthermore, the study also indicates that it is not advisable to consume turnip cultivated in an environment that exceeds safe Cd levels.